A beauty refined [large type] - Peterson, Tracie (Peterson, Tracie. Sapphire brides, 2016)
Phoebe Von Bergen is excited to accompany her father when he travels from Germany to purchase sapphires in Montana. Little does she know that her father's plans--for the gemstones and his daughter--are not what they seem. Ian Harper, a lapidary working in Helena, finds the young woman staying at the Broadwater Hotel more than a little intriguing. Yet the more he gets to know her, the more he realizes that her family story is based on a lie--a lie she has no knowledge of. And Ian believes he knows the only path that will lead her to freedom. Meeting Ian has changed everything. Phoebe is determined to stay in America, regardless of her father's plans. But she may not be prepared for the unexpected danger as the deception begins to unravel.